Zainal & Din Construction Sdn. Bhd. / Mohammad Syabil Azmi - Azmi, Mohammad Syabil (Faculty of Civil Engineering, 2019)
The motive of the industrial training are mainly to let the student to gather some of experiences from real time job for students to further studies onto higher degree. By letting the students experienced such things, the students are able to apply the knowledge that they have learnt from attending classes for theories and able to applied those theories into real life situation. Apart from fulfilling the mandatory requirement for programme Diploma of Civil Engineering, students should be able to emphasize all of the knowledge that they learn academically and success in use the knowledge for real life application such as in the job perspective. From this report, I have state and clarify all of the activities about how the internship going right from the beginning until the end of the internship programme. As for information, the students should attend the internship programme duration which are 2 months or 8 weeks. The company that I have undergoes my internship, Zainal & Din are managing 2 main projects which is Taman Perumahan Soga Sutera and also school construction at Kulai district in Johor. The site that I have been assigned to is Taman Perumahan Soga Sutera located at Batu Pahat district in Johor. This report also will have a details about the company background, the things that I have learnt and experienced and even the organizational structure of the company. During the internship programme, there are many problems that that have been encountered but it will also come with solution to solve the issues. I am hoping that this report will be able to assure the readers and should be easily to understand about the civil engineering field in job perspective